Somatic and psychological components of the static balance test in 10-15-year-old school children - Toth, L.; Sipos, K.; Bognar, J. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction The static balance is one of the most important sign of the psychomotor development in each age group. The preadolescence is that period when the biomechanic and psychological changes could result in both positive and negative effects in the motor performance. (Tóth, Sipos, 1998) The background factors of the static balance differences in the preadolescence were analyzed in our study separately for boys and girls in three different age groups (10-11-years, 12-13-years, and 14-15-years). Methods Motor tests (Static balance, 60 m dash, 10 m slalom run with ball, standing broad jump, Burpee-test, hip joint mobility test, and Cooper-test), and psychological measures (Tennessee Self-concept Scale: physical self-concept, and STAIC-H, A-State, A-Trait), and anthropometric measures (body height and body weight, BMI) were collected for 299 school children (132 boys and 167 girls). Results The boys' results are better than girls in all age groups for Cooper test and slalom run with ball. The hip joint mobility significantly better also in all age groups. 60m run and standing broad jump gender difference occurs only in group 2 and 3 in favor of boys. In group 3 (14-15-year of age) boys are better in Burpee test. There was no significant gender difference in the static balance in our sample. The static balance results show significant decrease with the age both for boys (p< 0.009) and girls (p< 0.017). The regression analysis shows that the physical self-concept and body height (for girls in group 1 and 2), and the physical self-concept and body weight (for boys in group 2) play determining role in the static balance model. Discussion/ Conclusions The gender differences in the motor performance become statistically significant from 12-13 years of age. The positive physical self-concept helps the static balance performance in preadolescents for girls. The elevation of the body height for girls, the increase of the body weight for boys has an unfavorable effect on the static balance.